When solving a system of equations by substitution, remember to remove the one variable and replace it with a quantity equal to that variable. For example, suppose the system is x = 2y + 3 and 3x + 4y = 16.
You can solve this system by substituting 2y+3 for x in the second equation. The second equation becomes 3(2y+3) + 4y = 16. Now we can solve for y.
6y + 9 + 4y = 16
10y = 7
y = 7/10
To solve for x, substitute 7/10 for y in the first equation. That gives us
x = 2(7/10) + 3
x = 14/10 + 3
x = 4.4